2019
DOI: 10.1002/est2.79
|View full text |Cite
|
Sign up to set email alerts
|

Performance analysis of the new design of photovoltaic/storage solar collector

Abstract: This study intends to develop a low cost, dependable, and efficient storage solar collector for household uses. This design is based on integrating solar cell technology and the solar storage collector into one system to achieve three objectives: water storage, electricity generation, and water heating. In this design, a solar cell was fixed on the inclined metal surface of a rectangular storage collector and acted as a black absorber surface. Two experimental models were constructed to study the performance o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 33 publications
1
4
0
Order By: Relevance
“…The average temperature of the water leaving the collector was 44 o C at 3 p.m. Results similar to the current results were recorded in several studies as[28] [13][29]. The value of solar radiation for Van city was shown in Fig.…”
Section: -1 Results Of the Storage Collector Under Iraqi Weather Consupporting
confidence: 89%
See 1 more Smart Citation
“…The average temperature of the water leaving the collector was 44 o C at 3 p.m. Results similar to the current results were recorded in several studies as[28] [13][29]. The value of solar radiation for Van city was shown in Fig.…”
Section: -1 Results Of the Storage Collector Under Iraqi Weather Consupporting
confidence: 89%
“…Taheri et al [12] used a layer of the black coloured sands immersed into the water storage tank to enhance the performance of the solar collector. The daily thermal efficiency was higher than 70% and the maximum temperature of the stored water into the collector was about 90 o C. Ahmed et al [13] presented a practical study for the execution of the rectangular storage collector as in Fig.5. The experimental and numerical outcomes confirmed that the proportion of absorbed area to storage water volume is an essential factor that influences on the performance of this type of storage solar heater.…”
Section: Introductionmentioning
confidence: 99%
“…The evaluation of indoor air quality monitoring systems, including sensor-based methods and IoT technologies are discussed in [32], complementing the design described. Additionally, [33] assesses the efficacy of a solar-powered air purifier with energy storage capabilities. A reference design for IoT systems is outlined in [34], emphasizing sensor integration and data analytics for efficient monitoring.…”
Section: Iot Based Purifiersmentioning
confidence: 99%
“…The overall efficiency from [32]: (10) = m ȧ Cp air (T a,out − T a,in ) (11) = ṁwcp water (T w,out − T w,in )…”
Section: Performance Calculationsmentioning
confidence: 99%